Strategic Climate Policy with Offsets and Incomplete Abatement : Carbon Taxes Versus Cap-and-Trade - Strand, Jon (2012)
This paper provides a first analysis of optimal offset policies by a "policy bloc" of fossil fuel importers implementing a climate policy, facing a (non-policy) fringe of other importers, and a bloc of fuel exporters. The policy bloc uses either a carbon tax or a cap-and-trade scheme, jointly with a fully efficient offset mechanism for reducing emissions in the fringe. The policy bloc is then shown to prefer a tax over a cap-and-trade scheme, since 1) a tax extracts more rent as fuel exporters reduce the export price, and more so when the policy bloc is larger relative to the fringe; and 2) offsets are more favorable to the policy bloc under a tax than under a cap-and-trade scheme. The optimal offset price under a carbon tax is half the tax rate; under a cap-and-trade scheme the quota and offset price are equal. The domestic carbon and offset price are both higher under a tax than under a cap-and-trade scheme when the policy bloc is small; when it is larger the offset price can be higher under a cap-and-trade scheme. Fringe countries gain by mitigation in the policy bloc, and more under a carbon tax since the fuel import price is lower, and since the price obtained when selling offsets is often higher (always so for a large fringe).